PENGARUH MODEL PEMBELAJARAN AKTIF GROUP TO GROUP EXCHANGE TERHADAP HASIL BELAJAR AKUNTANSI LANJUTAN DI PROGRAM STUDI PENDIDIKAN EKONOMI UNIVERSITAS HKBP NOMMENSEN PEMATANGSIANTAR - ELISABETH MARGARETA (JURNAL ILMIAH SIMANTEK, 2020)
This research was conducted to know and understand the influence of active learning model Group to Group Exchange onthe results of the study of advanced Accounting in Economics education program of HKBP Nommensen PematangsiantarUniversity. The method that the experiment uses. The population is a student of the economics education in semester 3 andtwo classes selected to be a research sample (class A and Class C), where one class is an experimental class while theother is a class of control. The research variables consist of free variables i.e. learning models and bound variables i.e. theresults of advanced accounting study students. Data collection tools in the form of observations, tests, and documentation.The data used in this study are pre-test and post-test class of experimental and class control student in 3rd semester ofEconomics Education course at HKBP Nommensen Pematangsiantar University. The test results of the test result of 35students were obtained that: all the questions are valid, the results of the study of the religious students, test questions havea level of difficulty is easy, moderate and difficult, and for the different power there are in the category so well, well, enoughand bad, hypothesis testing results with test Paired Sample T Test shows the value of Sig. (2-tailed) = 0,000, where if theprobability (Asymp. Sig) is < 0.05 then Ho is rejected and H1 is accepted, meaning there is a significant difference betweenthe student learning outcomes taught by the lecturer with using a learning model Group to Group Exchange compared withthe results of student learning if using the lecture learning model in the course of advanced accounting students semesterthree courses of study economics education HKBP Nommensen Pematangsiantar or can be concluded that there is apositive influence model active learning Group to Group Exchange against the results of the study of advanced accounting ofsemester three students at the Economics education program HKBP.